Tradição, tradução, hibridismo e resistência da identidade afro-brasileira na literatura amadiana - Nascimento, Aline Santos de Brito (2017)
It studies the Afro-Brazilian identity in the literature of Jorge Amado, through the characterization of traits of tradition, introduction, hybridism and resistance. It justifies that the analysis of the characteristics of the Afro-Brazilian ethnic group are vectors for the critical formation of the citizen and the valorization of those who identify with him. The new and the old, the global and the local are paradigms that mix them in the compositions under analysis, allowing the observation of Afro-Brazilian culture from a less conservationist line, recognizing the evolution of identities, which is the problem of this research. The general objective is to analyze the evidences of tradition, introduction and hybridism present in the Afro-Brazilian literature of Amado. The specific objectives are to characterize the literature of Amado; to identify the traits of Afro-Brazilian identity and resistance; and to analyze aspects of tradition and introduction that allow to classify them as hybrids. The methodological procedures include the collection of data with bibliographic research. The analyzes include the thematic axes tradition/innovation, symbology; space/time, territoriality and temporality; and social actors. The theoretical assumptions mainly discuss concepts such as displacement, marginal, race, class, gender, cultural traditions and hybrid (BHABHA, 2001); identity, collective memory, power, religion and culture (CASTELLS, 1999); ethno-racial characteristics of black person (SCHWARCZ, 1993); binary logic black/white; autochthonous/foreign; me/other (BERND, 2003); candomblé (SALAH, 2008); black woman and how to deal with the body (SACRAMENTO, 2012); and mulatto woman as a result of clandestine lovemaking (GUMÉRY-EMERY, 2004). Also it discusses "frontiers" of literature, fiction and non-fiction (BOSI, 2013); dialogues reinforced by the contemporary novel (BAKHTIN, 1998); desire to remake history (CERTEAU, 2011); theory of reception (MAINGUENEAU, 2001); search for identity and ethnocentrism (TODOROV, 1989); black literature (ALVES, 2002); silence of the marginalized (DALCASTAGNÈ, 2012); blacks denouncing slavery and/or exclusion (RIBEIRO, 2012); resistance (LIMA, SOUZA, 2016); love to land, topophilia (TUAN, 1980); resistance in the literatura of Amado (TEIXEIRA SOBRINHO, 2015); black culture in the literature of Amado (SOUZA, 2007); and defense of miscegenation (PATRÍCIO, 1999). The analyzes present: the discussion "Between the introduction and the tradition: marks of the black identity in Jubiabá" and alert about minority groups that seek the right to have voice and space in an engaged way in social questions; activism in the social movement; respect to cultural identities; and criticism of hegemonies. Investigate "Black identity and eroticism in Gabriela, clove and cinnamon", black and mulatto characters and their relationships of desire, love, passion and eroticism; semantic field of eroticism, and sensuality of the black ethnicity as discourse of the national imaginary. And the results of the study "Tent of miracles: the black intellectual and militancy against the racist elite”, thet clarify that works of Archanjo, mestizo, poor, are only recognized from the interest of a foreigner; and his books represent prejudice, violence and intolerance of whites about the rituals of African origin. The analyzes lead to the conclusion that the respect for diverse cultural identities must be propagated through the dissemination of literature. The results of the research confirm the hypothesis that the literature contributes to the critical formation of the citizen and the valorization of ethnic minorities.